Muon-spin relaxation and AC magnetometry study of the ferrimagnet LaSr2Cr2SbO9 - Hunter, E; Battle, P; Blundell, S; al., E (Elsevier, 2019)
AC susceptibility and muon spin relaxation data have been collected from a polycrystalline sample of LaSr2Cr2SbO9, a perovskite-like compound wherein the unequal distribution of Cr3+ and Sb5+ cations over two crystallographically-distinct six-coordinate B sites results in the onset of ferrimagnetism at ∼150 K. The data are used to elucidate the dynamics of the ferrimagnetic domain walls, thought to lie in Sb-rich regions, and suggest an energy barrier of ∼0.13 eV to their motion. The muon data confirm that the ferrimagnetic order is a true bulk phenomenon. The behaviour of this material is briefly compared to that of Ni2+- based relaxor ferromagnets.